Multi-criteria Analysis for the Selection of Sites Suitable for PV Solar Power Plants Connected to the Electricity Network in Northern Benin - ZOGBOCHI, Victor (My University, 2024)
This article presents the results of a multi-criteria analysis for the selection of sites suitable for photovoltaic (PV) solar power plants connected to the electricity grid. This work focusses on the combination of many criteria namely among others: distance to electric substation, maximum power producible, meteorological conditions, overall cost of energy to determine the most suitable solar PV that can produce power into the main electric grid. The evaluation of the suitability of the sites is carried out by the combination of a Geographic Information System (GIS) and the Analytical Hierarchy Process (AHP) approach. In this process, nine (9) factors to determine potential sites. By using the Technique of Order of Preference by Similarity with the Ideal Solution (TOPSIS), the distances were optimized for the identification of the best favorable sites. Lastly, the financial analysis is carried out by evaluating and comparing the Levelized Cost of Energy (LCOE) of each predetermined site to choose the most emblematic and profitable one. The results proved that the most relevant emblematic sites from a technical and economic point of view are the solar power plants of Parakou (20 MW), Djougou (20 MW) followed by those of Bembereke (10MW), Kandi (10 MW) and Natitingou (5MW) which respectively have the lowest LCOEs in descending order. The scenario that presents the lowest LCOE is the Bifacial 1-axis follower scenario followed by the 1-axis follower.
Keywords: Multi-Criteria Analysis; Solar Power Plants; Electric Grid; Economic Analysis; Levelized Cost of Energy